4u-12=0

Simple and best practice solution for 4u-12=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4u-12=0 equation:


Simplifying
4u + -12 = 0

Reorder the terms:
-12 + 4u = 0

Solving
-12 + 4u = 0

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 4u = 0 + 12

Combine like terms: -12 + 12 = 0
0 + 4u = 0 + 12
4u = 0 + 12

Combine like terms: 0 + 12 = 12
4u = 12

Divide each side by '4'.
u = 3

Simplifying
u = 3

See similar equations:

| 7(t+4)-3(l+t)=-19 | | 3x-6+4x+2=12 | | -7p+7p= | | (x/6)-(3x/2)=x/12 | | 3(a+3)-1=h(a+3) | | c(c-4)3(c-4)=0 | | 8=72 | | f(-x)=2x-4 | | 21+37=9+3j | | 3*8=4(-2+8) | | ln(7x)=-1 | | 38=4(-2+8) | | -3y-6x=-9 | | 83+7=5m+16 | | 9x+8y=32 | | Z/3-7=-1 | | f(5)=2x-4 | | 30-3x=20+7x | | X^2-38=4x | | (5x/8)-2=(7x/12) | | 2cosx-secx=0 | | X^3+x^2+x+16=0 | | (X+3)=4 | | 3x+4-3+2(x+1)=10 | | -2(3v-1)+2v=8+2(5v-8) | | y=-2x+-10 | | 20x^2-85x+20=0 | | 30-3x=20x+7x | | 15x+8=y+13 | | 78+15m=213 | | 6.5a+14=85.5 | | 24n-39=273 |

Equations solver categories